Preoperative significance of thyroglobulin, thyroid stimulating hormone and thyroglobulin antibody in differentiated papillary thyroid carcinoma - Rageh, Tarek M.; Abdou, Asmaa G.; Elkhouly, Enas A.; Abou El- Ela, Dalia H.; Zidan, Mohamed A. (International Surgery Journal, 2019)
Background: The objective of the study was to compare the levels of preoperative thyroglobulin (TG), thyroid stimulating hormone level (TSH), FT3, FT4 and TG Ab among 50 malignant and 50 benign thyroid swellings. Papillary thyroid cancer (PTC) is the most common malignancy in thyroid gland. TG antibodies (Ab) occur in around 20% of patients with papillary thyroid cancer (PTC), and the presence of TG Ab complicates the follow-up of these patients because TG-Ab interferes with the assay of serum TG7. Methods: A prospective and retrospective study conducted on 100 patients with thyroid nodule diagnosed by neck ultrasound and confirmed by histopathological evaluation in Faculty of Medicine, Menoufia University Hospital, Egypt, during January 2017 to July 2019. History taking, levels of TG, TSH free T3, free T4 and TG Ab, neck ultrasound or CT and pathological evaluation were done. Results: There were statistically significant differences between malignant and benign thyroid swellings regarding, TG level, TSH and T4 level. Also, there was statistically significant difference between the level of TG and tumor recurrence (p=0.01). While, there was no statistical significance between focality, staging, lymph node status, capsular invasion, lymphovascular embolization, and evidence of hashimoto thyroiditis and the level of TG. Conclusions: Preoperative serum TG concentration is a useful marker for predicting the presence of initial distant metastasis of PTC and tumor recurrence. TSH level considered an important prognostic factor for papillary thyroid cancer patients.